2023
DOI: 10.32996/ijels.2023.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using AR Technology on Language Learning

Abstract: The recent emergence and popularity of digital tools related to Augmented Reality (AR), such as Roar or Aumentaty, has facilitated the integration of this breakthrough technology in Language Learning, particularly in English as a Foreign Language (EFL). Thanks to the recent worldwide availability of new technological devices, such as tablets and smartphones, AR applications can be effectively used today in language learning with different learning purposes, such as grammar or enhancing the student’s listening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Marrahí -Gómez sought to analyze and review recent trends in AR implementation within English as a Foreign Language Classrooms (EFL) and present key projects focused on English instruction through AR-based initiatives published in WOS and Scopus in recent years. While many studies have shown that augmented AR technology is beneficial in enhancing students' motivation to learn, there has been little research on how AR technology increases students' motivation to learn English [22]. The Attention, Relevance, Confidence, Satisfaction (ARCS) framework was utilized.…”
Section: Application Of Ar In Englishmentioning
confidence: 99%
“…Marrahí -Gómez sought to analyze and review recent trends in AR implementation within English as a Foreign Language Classrooms (EFL) and present key projects focused on English instruction through AR-based initiatives published in WOS and Scopus in recent years. While many studies have shown that augmented AR technology is beneficial in enhancing students' motivation to learn, there has been little research on how AR technology increases students' motivation to learn English [22]. The Attention, Relevance, Confidence, Satisfaction (ARCS) framework was utilized.…”
Section: Application Of Ar In Englishmentioning
confidence: 99%
“…The process of AR involves superimposing virtual entities onto real-world images captured by cameras, thus engendering a distinct sense of reality when compared to Virtual Reality (VR) [5]. Its applications are widespread, encompassing domains like industry, education, healthcare, and language acquisition [6][7][8]. AR applications create a three-dimensional reality that presents the digital world as a tangible phenomenon, thereby offering solutions to the challenges encountered by students [6].…”
Section: Introductionmentioning
confidence: 99%